Evaluation of stress patterns in teeth with endodontic treatment and periapical lesions as abutments for fixed prosthesis: a finite element analysis study - Simay Koç; Ömer Kırmalı; H. Kürşat Çelik (BMC Oral Health)
Abstract Background Examining stress distributions in abutment teeth with periapical lesions is essential for understanding their biomechanical impact on dental structures and tissues. This study uses finite element analysis (FEA) to evaluate these stress patterns under occlusal forces, aiming to enhance treatment strategies and prosthetic designs. Methods Three FEA models were created: a healthy mandibular premolar (Model 1), a premolar with a single crown and a lesion repaired using a fiber-post (Model 2), and 3) a premolar with a lesion repaired using fiber-post to support a four-member bridge (Model 3). A 300 N occlusal static stress was given to each model at a 45° angle to the long axis of the tooth, namely at the lingual inclination of the buccal-cusp. Deformation behaviour and maximum equivalent stress distributions were simulated on the all components, including the bony structure for each model. Results The study showed a reduction in equivalent stress levels in trabecular and cortical bone, crown, cementum, and PDL under occlusal force, from Model 1 to Model 3. The Von Mises yield criteria values of the tooth models differed depending on the prosthetic restorations, with the highest value seen in Model 2 (133.87 MPa). Similar locations in all models showed concentrated equivalent stresses for all components. The periapical lesion area exhibited relatively low stress values for Models 2 and 3, at 0.061 MPa and 0.039 MPa, respectively. The largest level of stress was seen in the cervicobuccal areas of the tooth in all models. Conclusion Prosthetic restorations on teeth with periapical lesions resulted in varying stress and biomechanical responses in the tooth and surrounding bone tissue. These teeth can serve as abutments in a four-unit bridge when subjected to optimal occlusal stresses, based on the findings.